ANALYSIS OF THE CONCEPT OF THE PRINCIPLES GENERALLY ACCEPTED ACCOUNTING OF UNITED STATES OF AMERICA (FASB RULES) - Vílchez Olivares, Percy Antonio (2009)
The Framework for the preparation and presentation of financial statements is a statement that directs and informs the accounting principles generally accepted in the United States (U.S. GAAP), which in turn is valid in our country, on the application to determine the accounting principles generally accepted in Peru, in its supplementary nature as established by Resolution No. 013-98 Accounting Standards Council, an organ of the Public Accounts of the Nation. The Framework is the backbone of a regulatory system in the process of issuing and development of new standards. The policy advice of international standard American Standard IASB and FASB have initiated since 2006 a joint project to improve and align their framework with the aim of achieving a set of high quality standards, enabling push-based convergence financial information is presented and also contribute to the free flow of capital in various markets. This article presents an analytical study on the framework of the rules issued by the Financial Accounting Standards Board FASB applies for Peruvian companies that report to its parent company headquartered in the United States and report to the Securities and Exchange Commission that country.